2016
DOI: 10.1016/j.cell.2016.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria: Masters of Epigenetics

Abstract: Accumulating evidence argues that aging exerts a profound influence on epigenetics, and vice versa. A pair of studies by Merkwirth et al. and Tian et al. now provide insights on how mitochondrial stress experienced by C. elegans larvae propagates a specific and persistent epigenetic response that protects adult cells and extends lifespan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 9 publications
(13 reference statements)
0
15
0
Order By: Relevance
“…Furthermore, FOXO3a regulated Pink-1 transcription in human cells (42). This adds to the growing evidence that epigenetic factors could well contribute to aging and dementia (69,70).…”
Section: Pink-1 Regulation By Presenilinsmentioning
confidence: 69%
“…Furthermore, FOXO3a regulated Pink-1 transcription in human cells (42). This adds to the growing evidence that epigenetic factors could well contribute to aging and dementia (69,70).…”
Section: Pink-1 Regulation By Presenilinsmentioning
confidence: 69%
“…In summary, we showed for the first time that alterations in basal and ATP-linked OCR (but not other specific mitochondrial parameters), in the critical third larval developmental stage, represent a potential predictor of lifespan extension in response to mitochondrial stress, and that these changes most likely precede pro-longevity reprogramming processes ( Figure 4). Although changes in basal and ATP-linked OCR may simply correlate with lifespan extension, due to the observed very strong correlation, it is instead likely that these may promote metabolic, genetic and epigenetic reprogramming later in life [18][19][20], which are, in fact, causally involved in longevity specification. Thus, as opposed to the metabolic inflexibility associated with cellular senescence [21,22] and the detrimental effects observed across species at the cellular and organismal level upon severe mitochondrial dysfunction [23], mild mitochondrial stress leads to less profound alteration of mitochondrial functional parameters.…”
Section: Discussionmentioning
confidence: 99%
“…An initial clue that the lifespan extension is indirect came from the observation that activating the UPR mt only extends lifespan if the activation occurs during the larval developmental stages, while lifespan is not extended if UPR mt activation occurs solely in adults . It was subsequently found that during larval stages, UPR mt in neurons triggers a systemic response that induces changes in chromatin in other tissues, and the altered transcriptional changes mediate lifespan extension . Therefore, the UPR mt lifespan extension is not directly associated with the ETC dysfunction (but instead arises from secondary transcriptional changes).…”
Section: Is Increased Mitochondrial Fusion a Proxy For Increased Enermentioning
confidence: 99%